ANALYSIS OF SALMONELLA SP. CONTENT IN BROILER MEAT FROM RPA & TPA IN BANJARBARU CITY: broiler, microbial contamination, traditional market, Salmonella sp. - Herliani, Herliani; Habibah, Habibah; Hidayat, M. Ilmi (TROPICAL WETLAND JOURNAL, 2023)
The purpose of this research is to detect the presence of Salmonella sp. bacteria contamination in broiler meat sold in TPA and RPA Banjarbaru. This study used a survey method with purposive sampling technique, with a total of 92 samples (2 from TPA and 2 from RPA). The research was conducted at 2 Broiler Slaughterhouses (TPA) and 2 Broiler Cutting Houses (RPA) in Banjarbaru City, followed by testing at the Laboratory of the Regional Veterinary Disease Investigator Testing Center for the Kalimantan Region. In TPA 1 Loktabat Utara, 22 samples were positive for Salmonella sp. out of 22 samples. Then, in TPA 2 Guntung Payung, 6 samples were positive for Salmonella sp. out of 22 samples, while in RPA 1 Guntung Manggis, none of the 24 samples tested positive for Salmonella sp., and in RPA 2 Landasan Ulin Timur, 2 samples were positive for Salmonella sp. out of 24 samples tested. In conclusion, out of 92 samples, the tested broiler meat originated from 2 TPA and 2 RPA. Positive Salmonella sp. samples were 63.6% in TPA and 4.16% in RPA.